2017
DOI: 10.7860/jcdr/2017/22767.9305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cone Beam Computed Tomography-Derived Alveolar Bone Density Between Subjects with and without Aggressive Periodontitis

Abstract: Alveolar bone density as measured by CBCT in aggressive periodontitis patients was not different from periodontally healthy individuals. Further studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Similarly, Öztürk et al, 25 using dual-energy X-ray absorptiometry, found that the mandibular bone mineral density of the periodontally healthy individuals was higher than that in the periodontitis group. Al-Zahrani et al, 24 using CBCT in a Saudi Arabian population, found that alveolar bone density was different between the individuals with and without aggressive periodontitis; however, their result was not statistically significant.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, Öztürk et al, 25 using dual-energy X-ray absorptiometry, found that the mandibular bone mineral density of the periodontally healthy individuals was higher than that in the periodontitis group. Al-Zahrani et al, 24 using CBCT in a Saudi Arabian population, found that alveolar bone density was different between the individuals with and without aggressive periodontitis; however, their result was not statistically significant.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have evaluated mandibular bone mineral density and periodontitis. 14 , 24 , 25 , 28 , 29 Klemetti et al, 28 using dental radiographs, reported higher bone density in the regions affected by periodontitis. However, similar to our results, Von et al, 29 using dual-energy X-ray absorptiometry, found that severe periodontitis in young adults seems to be a local factor associated with relatively low bone mineral content in the jaws without systemic alterations of bone mineral content, bone mineral density, and bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies that did not belong to any level of efficacy were disregarded [51][52][53][54][55]. Studies that addressed bone density conducted by Al Zahrani et al [56] and bone coverage conducted by Ferriera et al [57] were also excluded. Published studies by Evangelista et al [58], Sun et al [59], and Leung et al [60] discussed only the naturally occurring dehiscence and fenestration, hence, they were disregarded.…”
Section: Studies Allocationmentioning
confidence: 99%
“…In orthodontics and periodontics, there are applicable methods to explore the development of bone resorption and recession. Al-Zahrani et al (2017) and Zhang et al (2020) used CBCT data to analyze the progression on of periodontitis disease. For example, the patient's alveolar bone shrinks owing to disease progression, and may cause multiple teeth to move or loosen.…”
Section: Introductionmentioning
confidence: 99%